Intravenous regional block is similar to sympathetic ganglion block for pain management in patients with complex regional pain syndrome type I - Nascimento,M.S.A. (2010)
Sympathetic ganglion block (SGB) or intravenous regional block (IVRB) has been recommended for pain management in patients with complex regional pain syndrome type I (CRPS-I). Forty-five patients were initially selected but only 43 were accepted for the study. The present study evaluated the efficacy of IVRB produced by combining 70 mg lidocaine with 30 µg clonidine (14 patients, 1 male/13 females, age range: 27-50 years) versus SGB produced by the injection of 70 mg lidocaine alone (14 patients, 1 male/13 females, age range: 27-54 years) or combined with 30 µg clonidine (15 patients, 1 male/14 females, age range: 25-50 years) into the stellate ganglion for pain management in patients with upper extremity CRPS-I. Each procedure was repeated five times at 7-day intervals, and pain intensity and duration were measured using a visual analog scale immediately before each procedure. A progressive and significant reduction in pain scores and a significant increase in the duration of analgesia were observed in all groups following the first three blocks, but no further improvement was obtained following the last two blocks. Drowsiness, the most frequent side effect, and dry mouth occurred only in patients submitted to SGB with lidocaine combined with clonidine. The three methods were similar regarding changes in pain intensity and duration of analgesia. However, IVRB seems to be preferable to SGB due to its easier execution and lower risk of undesirable effects.